Current Status Of ScientificMethodical Support For The Development Of Information And Communicative Competence Of Future Engineers And Ways To Improve It (Eurasian Research Bulletin, 2026)
This in the article future engineers informational and communicative competence develop process provider scientific and methodological of supply current status analysis Modern digital education in the environment engineering education efficiency in increasing informational and communicative competencies important factor is considered. In the study engineering in education being used methodical approaches, educational-methodical materials, electronics education resources and pedagogical technologies analysis Also, scientific and methodological supply improvement main directions , digital education from the means use opportunities and education to the process innovative methods current to grow issues illuminated . Research results future engineers informational and communicative competence develop process effective organization to reach service does.